The role of Intrinsic Motivation On Innovative Work Behavior Mediated By Creative Self-Efficacy - Febi Herbiyanti; Indah Rahmawati; Dharliana Ayu Hardjowikarto (Publikasi Indonesia, 2024)
This study aims to examine the role of Intellectual Motivation on Innovative Work Behavior through Creative Self-Efficacy mediation in rattan craftsmen in Tegalwangi Village. In this study using a type of quantitative research method. This study examines and analyzes the role of creative self-efficacy as an intervening variable in intrinsic motivation and its effect on innovative work behavior. With a total sample of 103 rattan craftsmen in Tegalwangi Village. Data collection techniques include questionnaires, interviews, and observations. The measurement scale used in this study is using a Likert scale of 1 to 5 with categories strongly disagree, disagree, neutral, agree, and strongly agree. The analysis technique in this study is SEM (Stuctural Equation Modeling) with PLS (Partial Least Square) Program version 4. The results showed a significant influence of intrinsic motivation on creative self-efficacy, creative self-efficacy on innovative work behavior, intrinsic motivation on innovative work behavior, and creative self-efficacy partially mediated between intrinsic motivation and innovative work behavior in rattan craftsmen in Tegalwangi Village.